Optimal Local Government Size for Maximizing Regional Economic Growth: A Case Study of Regencies and Cities in Indonesia - Pradana , Hasta Dwi (Jurnal Economic Resource, 2024)
This study examines the relationship between local government size and regional economic growth in Indonesia's regencies and cities during 2011–2022. Using panel data regression models, including Fixed Effects Model (FEM), we find that an optimal government size of approximately 73.56% of GRDP maximizes economic growth. Results indicate diminishing returns beyond this threshold, while investment emerges as a critical growth driver. Data sourced from official government statistics ensure robust analysis. Findings emphasize the need for policies optimizing government expenditure and enhancing investment to foster sustainable development. Future research could explore institutional and human capital dynamics.